The Impact of Teacher’s Reinforcement on Students’ Engagement in English Language Learning (Tamaddun, 2025)
This study explores the impact of teacher reinforcement on student engagement in English language learning at SMPN 40 Makassar. Framed within a descriptive qualitative research design, data were gathered through classroom observations and semi-structured interviews involving one English teacher and seven eighth-grade students. The findings reveal that the teacher employed a variety of verbal and non-verbal reinforcement strategies such as praise, encouragement, eye contact, gestures, and rewards to cultivate a positive and supportive learning environment. From the teacher’s perspective, reinforcement enhanced students’ confidence, encouraged participation, and positively influenced classroom dynamics. Students echoed this view, identifying reinforcement as a key motivational factor that increased their interest, reduced anxiety, and promoted their willingness to engage in classroom activities. The analysis further suggests that reinforcement not only supports behavioral engagement (active participation) but also fosters emotional (enjoyment, confidence) and cognitive (focus, effort) engagement. These results are interpreted through the lens of Skinner’s Operant Conditioning Theory, Bandura’s Social Learning Theory, and Self-Determination Theory by Deci and Ryan, which collectively emphasize the importance of motivation, autonomy, and social connectedness in learning. The study concludes that teacher reinforcement plays a pivotal role in sustaining student engagement across multiple dimensions. It underscores the need for intentional and consistent use of reinforcement strategies that are sensitive to student diversity and classroom context. These findings hold valuable implications for English language educators seeking to create more inclusive, motivating, and learner-centered environments, particularly within junior high school EFL classrooms in Indonesia.